2008
DOI: 10.3121/cmr.2008.813
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation as a Treatment Option for Intractable Neuropathic Cancer Pain

Abstract: Nearly 6,750,000 people suffer moderate to severe cancer-related pain each year. Unfortunately, 10% to 15% of these patients fail to achieve acceptable pain relief with conventional management. Spinal cord stimulation (SCS) has been used with increased frequency for successful treatment of intractable cancer pain. We present two cases of intractable, refractoryto-conventional treatment cancer pain that were successfully treated with SCS. Case 1 reports a 51-year-old male with burning pain at the left groin sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 17 publications
0
30
0
Order By: Relevance
“…SCS stimulation has also been used in the mid thoracic area and could achieve pain relief, even for groin pain. There was an improvement of more than 80% . The effects of DRGS used for pain in the leg and groin were examined in an important study which also showed good results .…”
Section: Discussionmentioning
confidence: 99%
“…SCS stimulation has also been used in the mid thoracic area and could achieve pain relief, even for groin pain. There was an improvement of more than 80% . The effects of DRGS used for pain in the leg and groin were examined in an important study which also showed good results .…”
Section: Discussionmentioning
confidence: 99%
“…7 Spinal cord stimulation has been used to successfully treat chronic pain in patients with failed back syndrome, 8,9 ischemic limb pain, 10 angina pectoris, 11 painful peripheral neuropathies, 12,13 and cancer related pain. 14,15 Spinal cord stimulation may be a therapeutic alternative for patients with combined urinary dysfunction symptoms and radicular low back pain who, in the past, exhausted all available treatments or failed test stimulation before the placement of the device for InterStim therapy. Spinal cord stimulation and InterStim therapy are considered to be minimally invasive surgical interventions that have successfully positioned themselves between more conservative medical treatments and more invasive surgical procedures which may have mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports applying spinal cord stimulation (SCS) at the T7‐T9 levels have indicated some applicability to chronic neuropathic groin pain, in some cases relieving 75% or more . However, a limitation of SCS with groin pain as with all axial pain distributions is that it is extremely difficult to achieve selective coverage of the painful regions; patients may find it necessary to tolerate “a pair of pants” of extraneous paresthesia in order to also capture the relatively discrete painful region.…”
Section: Literature Summary Of Drg Stimulation For Groin Painmentioning
confidence: 99%
“…57 A number of reports applying spinal cord stimulation (SCS) at the T7-T9 levels have indicated some applicability to chronic neuropathic groin pain, in some cases relieving 75% or more. [58][59][60] However, a limitation of SCS with groin pain as with all axial pain distributions is that it is extremely difficult to achieve selective coverage of the painful regions 61,62 ; patients may find it necessary to tolerate "a pair of pants" of extraneous paresthesia in order to also capture the relatively discrete painful region. It has been proposed that dorsal root ganglia (DRG) stimulation may be a pain management option 63 that is a viable alternative to SCS for this pain distribution, because the recruitment of distally projecting sensory neurons may be more precisely selected to achieve a limited region of paresthesia.…”
mentioning
confidence: 99%